Public-Private Collaboration in Sustainable Tourism Destination Management: Case Study of MaxOne Resort and Hotel Makassar - M. Yusuf Sandy, M. Yusuf Sandy (Journal of International Multidisciplinary Research, 2025)
Public-private collaboration is a vital strategy in managing sustainable tourism destinations, integrating diverse stakeholders to balance economic growth, environmental sustainability, and social equity. Despite the hospitality sector’s key role in tourism governance, research on its collaboration with public institutions, particularly in Makassar, Indonesia, remains limited. This study examines MaxOne Resort and Hotel Makassar to explore the mechanisms, challenges, and outcomes of public-private partnerships (PPPs) in sustainable tourism destination management (STDM). Using a qualitative case study approach, the research employs in-depth interviews, participatory observation, and policy analysis to investigate how MaxOne Resort collaborates with local government and communities to implement sustainability initiatives. The findings reveal that structured mechanisms such as formal agreements, joint projects, and stakeholder committees facilitate sustainable governance. MaxOne Resort actively engages in environmental conservation, community empowerment, and responsible tourism practices, positioning itself as a sustainability model within the hospitality sector. However, regulatory misalignments, funding constraints, and inconsistent stakeholder engagement present significant challenges. The study underscores the relevance of the Penta-Helix framework, highlighting how collaboration among government, private sector, academia, community, and media enhances the legitimacy and effectiveness of sustainability initiatives. This research contributes to the literature by providing a localized analysis of PPPs in Makassar, bridging the gap between theoretical models and practical applications. The findings offer policy recommendations to strengthen stakeholder collaboration, optimize governance structures, and support sustainable tourism development in emerging destinations.